Problemy wielokulturowości na Ukrainie - Sobieraj, Iwona (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
Since the proclamation of its independence Ukraine has been struggling with numerous serious social problems. They are partly inherited after the Soviet Union, but partly they reflect the processes emerging under the new social and political circumstances. The latter involve the growing social migration and particularly the migration of Crimean Tartars to the Crimea and the issues of appropriate ethnic relations between various ethnic groups in Ukraine. Both issues mainly concern the southern frontier of Ukraine and they are particularly intensive in the Crimea, which constitutes an Autonomous Republic of Ukraine. These processes create a highly complex national situation in the Crimea, which is outlined in the paper.